Use of GFRP as retrofit alternative for confined masonry walls with window opening subjected to in-plane lateral load. (15th November 2020) - Leal-Graciano, J. Martin; Quiñónez, Basilia; Rodríguez-Lozoya, Héctor E.; Pérez-Gavilán, Juan J.; Lizárraga-Pereda, José F.
Highlights: Experimental investigation of confined masonry walls with a central openings. The use of glass fiber reinforced plastic (GFRP) to reinforce the opening perimeter. It is feasible to use GFRP to reinforce the perimeter of openings on masonry walls. Contribution of GFRP to shear strength is similar than that of confinement elements. Contribution of GFRP to ductility is larger than that of confinement elements. Abstract: The results from an experimental campaign of four confined masonry walls subject to cyclic lateral load are presented. In every case, the wall included a central opening. The feasibility of using glass fiber reinforced plastic (GFRP) to reinforce the opening perimeter was studied. For this, the specimens had different reinforcement conditions in that zone. The first wall was not reinforced (control specimen), the second specimen was reinforced with tie-columns and tie-beams and the third specimen included GFRP surrounding the opening. In addition, the applicability of the GFRP on the rehabilitation of masonry walls with openings was studied. For this purpose, the nonreinforced wall after testing was repaired and tested again. The results indicate that the reinforced wall with GFRP composite had similar strength and stiffness and a larger ductility than the reinforced wall with the traditional system through tie-columns and tie-beams. The rehabilitated wall recovered the lateral strength, even though its stiffness was lower than the original wall.